Método de Implantação de um Sistema de Gerenciamento de Conteúdo Corporativo (ECM) em Pequena e Média Empresa (PME) - Ohashi, Fábio Kazuo (2017)
Unstructured content is growing exponentially, content is created, edit and stored on network folders or in the user computers. Enterprise Content Management (ECM) systems are adopted by many companies to share securely and manage properly all enterprise information and knowledge. Usually, only big companies adopt ECM systems but SMEs (Small, Mediums Enterprises) can benefit from a knowledge management ECM system. This master thesis goal is to propose an ECM implementation method for PMEs, based on Hullavarad, O’Hare e Roy (2015) model for big companies. An action search paradigm in a single medium size company was used. Also, semi-structure interviews, direct observation, and document analysis technics were applied. The resulting model highlight are that the most critical stages are a) Stage 1 - ECM Roadmap Strategy: phases ‘Business need’, ‘Need assessment’ and ‘Stakeholder buy-in’ b) Stage 2 - ECM Development: Phase ‘Test solution’. And none of stage 3 (ECM Deployment) phase has a critical level.